Klasifikace germinálních nádorů varlete - Motlík, K; Stejskalová, A; Abrahámová, J (Ceskoslovenska patologie, 1986)
Based on the collection of more than 500 personal as well as consiliary cases of TGCT and a thorough review of the existing classifications, the essential synonyms used for designating TGCT entities have been subjected to a critical reappraisal. The tumour entities have been defined exactly to facilitate their coding according to the ICD-O system. The existing classification system have been subjected to a critical reappraisal and compared one to another as well as to our own classification as suggested by ourselves in 1974 and used since then. A detailed discussion and exact coding of well-defined entities is believed to permit an almost complete interconvertibility of the most significant classifications with that of ours and thus to form a reliable basis for amy form of comparison, including the therapeutic results. The bioptic examination of surgical specimens obtained by orchiectomy (other samples are regarded unsuitable) must be carried out in a standardized manner. This should permit not only the usual typing of the respective tumour but also the data necessary for proper tumour staging which today appears to be a natural prerequisite for rational treatment and its monitoring. The main principles of bioptic examination of testicular tumours have been summarized in brief.
Keywords: Neoplasms, Germ Cell and Embryonal; lidé; mužské pohlaví; Male; testikulární nádory; Testicular Neoplasms; germinální a embryonální nádory; Humans